Zamiast Szymborskiej? Krystyna Miłobędzka i źródła współczesnej ekopoezji w Polsce - Skurtys, Jakub (Przestrzenie Teorii, 2018)
The paper deals with the topic of ecologically oriented poetry of Krystyna Miłobędzka as a vital tradition for 21st-century Polish ecopoets. The author tries to trace the changes in the poetic canon after 1990 and shows the increasing interest in Miłobędzka’s poetry among modern poets. By analyzing mainly meta-poetic texts, the paper contrasts Miłobędzka’s posthumanistic, “event-driven” way of writing with the humanistic lyrical subject of Wisława Szymborska’s poetry. The author presents the former as more influential and more productive for modern, ecopoetic styles, including elements such as: waking the awareness, organic perspective of language, an egalitarian way of life and thinking about relations in categories of space and adhesion rather than domination.